2006
DOI: 10.1029/2006ja011901
|View full text |Cite
|
Sign up to set email alerts
|

Magnetohydrodynamic simulation of the interaction between interplanetary strong shock and magnetic cloud and its consequent geoeffectiveness: 2. Oblique collision

Abstract: [1] Numerical studies of the interplanetary ''shock overtaking magnetic cloud (MC)'' event are continued by a 2.5-dimensional magnetohydrodynamic (MHD) model in heliospheric meridional plane. Interplanetary direct collision (DC)/oblique collision (OC) between an MC and a shock results from their same/different initial propagation orientations. For radially erupted MC and shock in solar corona, the orientations are only determined respectively by their heliographic locations. OC is investigated in contrast with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 62 publications
3
44
0
Order By: Relevance
“…However, the presence of plasma material of CME1 trailing edge after the marked leading edge of CME2 cannot be denied, as the merging of both CMEs is in progress and continues beyond the Earth [ Liu et al , ]. The possibility of such mixing of CMEs have also been reported earlier which emphasize that signatures of CMEs interaction observed in situ depend on the relative orientation of the flux rope associated with both CMEs [ Xiong et al , , ; Lugaz et al , ; Lugaz and Farrugia , ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the presence of plasma material of CME1 trailing edge after the marked leading edge of CME2 cannot be denied, as the merging of both CMEs is in progress and continues beyond the Earth [ Liu et al , ]. The possibility of such mixing of CMEs have also been reported earlier which emphasize that signatures of CMEs interaction observed in situ depend on the relative orientation of the flux rope associated with both CMEs [ Xiong et al , , ; Lugaz et al , ; Lugaz and Farrugia , ].…”
Section: Resultsmentioning
confidence: 99%
“…However, only few studies have been dedicated to understand the role of interacting CMEs in the generation of geomagnetic storms (Burlaga, Behannon, and Klein, 1987;Farrugia et al, 2006;Xiong et al, 2006). Our study is important as it focuses on the role of interacting CMEs in the generation of geomagnetic storms as well as substorms.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, these interactions are of great importance from space weather point of view. Before the era of wide angle imaging far from the Sun, the understanding of involved physical mechanisms in CME-CME or CME-shock interaction was achieved mostly from magnetohydrodynamic (MHD) numerical simulations of the interaction of a shock wave with an magnetic cloud (MC) (Vandas et al, 1997;Vandas and Odstrcil, 2004;Xiong et al, 2006), the interaction of two ejecta (Gonzalez-Esparza, Santillán, and Ferrer, 2004;Lugaz, Manchester, and Gombosi, 2005;Wang et al, 2005), and the interaction of two MCs (Xiong et al, 2007;Xiong, Zheng, and Wang, 2009). have shown that a forward shock can cause an intense southward magnetic field of long duration in the preceding magnetic cloud.…”
Section: Introductionmentioning
confidence: 99%
“…A possible reason why the expansion rate is significantly below unity is that the MCs are perturbed by ambient solar wind and/or other transients as shown in observational statistics [ Gulisano et al , ], which may cause the external pressure surrounding the MC decreasing with distance more slowly than usual. The numerical simulations by, e.g., Xiong et al [, ], Lugaz et al [] also suggested that CME‐CME interaction may affect the expansion rate of the preceding CME.…”
Section: Statistical Properties Of Plasma Motionmentioning
confidence: 99%